Many paths to destruction: Family-specific turnover and stress responses for tRNA introns - Sara Metcalf; Regina T. Nostramo; Alicia Bao; Katherine Clark; Paolo L. Sinopoli; Anita K. Hopper (Proceedings of the National Academy of Sciences, 2026)
In organisms ranging from Archaea to humans, a subset of genes encoding tRNAs contain introns. Upon splicing, the tRNA exons are joined and the released free introns are rapidly degraded. Although tRNAs introns were previously considered to be “junk” sequences, we recently reported that free tRNA introns (fitRNAs) of Saccharomyces cerevisiae serve as negative regulators of the cellular levels of mRNAs that bear long stretches of open reading frame sequence complementarity to tRNA introns. We also reported that 2 of the 10 families of tRNA introns accumulate to elevated levels when cells suffer oxidative stress. The results led to the current investigations of the regulation of tRNA intron cellular levels. We document that tRNA intron turnover occurs by combinations of 5’ RNA kinases, 5’ to 3’ and 3’ to 5’ exonucleases as well as by at least three endonucleases and, generally, the levels of each tRNA intron family are regulated by a unique combination of nucleases/kinases. Similarly, one family of excised intron forms circles whereas the other free tRNA intron families do not. Further, levels of individual tRNA introns differ in response to environmental conditions including type of media, stage in growth curves, and exposure to elevated temperature. Together, the findings highlight the many cellular pathways utilized to regulate tRNA intron levels and the specificity of these pathways for different tRNA families and varying cellular conditions. The results underscore the likely important roles of the discovered individual fitRNAs in regulation of cell biology and responses to environmental conditions.